2020
DOI: 10.4103/jfmpc.jfmpc_893_20
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of understanding about human papilloma virus vaccination among undergraduate medical students in a developing country: Perspective from India

Abstract: Background and Aims: Human papilloma virus (HPV) infection is the most common sexually transmitted infection responsible for cervical cancer in women. There is no cure for HPV but safe and effective vaccinations before sexual debut can definitely decrease the incidence of cervical cancer. This research aims to explore the basic understanding of medical students about cervical cancer, HPV and HPV vaccination. Methods and Material: This was a descriptive, questionnaire ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Similar to other studies that show the majority of medical and health science students have great knowledge. 25,27 Even so, some studies don't align as they state that a larger part of students have lack or poor knowledge, but i t is positively associated with academic years and age. 16,24,28 Previous studies found that even though male and female students have medical education as their main source of knowledge, female students have a better understanding of HPV infection and vaccines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to other studies that show the majority of medical and health science students have great knowledge. 25,27 Even so, some studies don't align as they state that a larger part of students have lack or poor knowledge, but i t is positively associated with academic years and age. 16,24,28 Previous studies found that even though male and female students have medical education as their main source of knowledge, female students have a better understanding of HPV infection and vaccines.…”
Section: Resultsmentioning
confidence: 99%
“…16,24,28 Previous studies found that even though male and female students have medical education as their main source of knowledge, female students have a better understanding of HPV infection and vaccines. 27,29,30 Some explained that it is because females have more interest in the topic that leads to higher grades. 27 This study founds that many students have 31 Other studies also discovered that albeit medical students have better knowledge and express higher awareness, it is still considered poor and doesn't influence the vaccination rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 ] Currently, epidemiological survey data provide important insight since the time of vaccine licensed in the country less than 20% of females have been vaccinated against HPV downplaying the benefits of the vaccination. [ 10 11 12 ] Furthermore suboptimal uptake of screening among Indian women. [ 13 14 ]…”
Section: Introductionmentioning
confidence: 99%